An unusual presentation of a retroperitoneal cyst. (3rd November 2014) - Sarkar, Debashis; Gulur, Dev; Patel, Snehal; Nambirajan, Thiagarajan
Abstract : A 34-year-old woman presented to the surgical assessment unit with severe right loin to groin pain. An ultrasound scan of the abdomen revealed a complex cyst in the right iliac fossa and a subsequent CT scan revealed a 7.5 cm retroperitoneal cystic lesion below the lower pole of the right kidney. The patient also had MRI of the kidneys, which confirmed the finding. The image showed the cyst was not attached to the kidneys and was clearly separate. She underwent a laparoscopic excision of the cyst. Histopathology revealed a cyst lined by a single layer of mucinous epithelium of endocervical type with foci of calcification and hyalinisation on the wall. The cyst was thought to be a benign cyst of Mullerian origin.